Strategic stability at 30+ years: stasis, evolution, or degradation? - D. V. Stefanovich (Международная аналитика, 2021)
“Strategic stability” as a characteristic of military and political relations with a low possibility of large-scale armed confl ict between great powers remains one of the basic notions of international security, especially in its nuclear missile dimension. At the same time, this notion also sets forth tangible state of strategic forces of two (or potentially more) nations and the framework of risk reduction and arms control measures preventing a nuclear war. The purpose of this study is to identify the main trends in this area and how strategic stability can be maintained and enhanced. To this end, I review the main offi cial doctrinal documents and statements in this area, international arms control treaties, trends in the development of the armed forces, and academic and expert publications. It is concluded that strategic stability can be preserved under increasing infl uence of a growing number of new factors, both political (including degradation of arms control regimes) and technological. Among the latter are modernization and development of means for delivery of nuclear warheads, growth of long-range precision-guided non-nuclear weapons potential, increase of antagonism in new environments. The experts point out the need for active work of the academic community and diplomats to fi nd new solutions ensuring maintenance of strategic stability in the future. Negative scenarios are outlined in the absence of such solutions.